Phenotypic and genomic characterization of Kedah-Kelantan bulls and comparative assessment of semen characteristics - Sirajul, Islam Mohammed (2022)
Kedah-Kelantan (KK) cattle are a well-adapted indigenous cattle breed in Malaysia. Despite having a slower growth rate than crossbred cattle, synthetic breeds, and imported beef breeds, KK cattle represents the primary source of more than 63 percent of domestic beef production in Malaysia. Nevertheless, purebred KK cattle are suffering from major germplasm dilution issues because of the current widespread and haphazard crossbreeding practices. The phenotypic and genomic characterization have not yet been recorded in order to prevent genetic dilution and further genetic improvement of this potential KK breed. The second source of domestic beef production in the country is various crossbred cattle. One of the most important crossbred cattle is the KK crossed with Brangus bulls. Although there are few studies on the growth, scrotal or testicular biometry, and semen characteristics of KK bulls, a comparative study with KK x Brangus bulls at a young age has not been addressed yet. Therefore, this study was conducted to determine the phenotypic and genomic characterization of Malaysian KK bulls and their semen characteristics in comparison to KK x Brangus bulls. A total of 184 purebred KK cattle were visually assessed for phenotypic features across three distinct agro-ecological zones. Fifty-one purebred KK cattle, regardless of sex, were measured for morphometric traits. The genomic DNA samples of two purebred KK bulls were sequenced using the Illumina NovaSeq 6000 platform after library construction. The sequence alignment, read mapping, assembly, and variant calling steps were all completed using the standard bioinformatics pipeline. For the whole genome resequencing of this investigation, the bovine reference genome located from https://www.ncbi.nlm.nih.gov/assemly/GCF 000247795.1 was utilized. Various software were used to determine existence of genomic variants in KK bull’s genome. Monthly body weight (BW) and scrotal testicular biometry were measured from 10 experimental bulls consisting of 6 purebred KK and 4 KK × Brangus bulls. Sperm chromatin condensation (SCC) and sperm DNA integrity of 48 frozen semen samples were measured by using the aniline blue (AB) and acridine orange (AO) test, respectively. One hundred twenty blood samples were assessed for testosterone (T), Gonadotrophin releasing hormone (GnRH), and insulin–like growth factor 1 (IGF1) of the experimental bulls. Puberty was defined when a bull produces an ejaculate containing a minimum number of 50×106 sperm cells with a minimum of 10% motility. Data were analyzed using SPSS computer software program. Brown was the predominant coat color in KK cattle with small body size. The overall means of wither height, heart girth, and body length in KK were 104.30±7.13 127.41±13.16, and 98.30±12.27cm, respectively. The genomic part of the study on the two KK bulls revealed an average number of single nucleotide polymorphisms (SNPs), insertions and deletions (InDels), structural variations (SVs), and copy number variation (CNVs) of 8,823,792 (85%); 1,573,661 (15%); 30,547 (0%), and 24,254 (0%), respectively. Moreover, out of 57,855 SNPs found in the gene coding regions of KK bulls, 35,093(61%), 22,608 (39%), 212(0%), and 42 (0%) for synonymous, non-synonymous, stop gain and stop loss, respectively. The functional classification of InDels such as deletion and insertion, were 848,972 (54%) and 722,563 (46%), respectively. On the other hand, the comparison between the KK and KK× Brangus bulls uncovered significantly greater (p˂0.05) body weight in KK× Brangus bulls (230.50± 9.32kg) than KK bulls (204.50±13.22 kg) at 24 months of age. Moreover, this study also showed that conventional semen quality, SCC, and sperm DNA integrity were significantly (p˂0.05) greater in KK bulls than in their crossbred bulls. At the age of 18 months, the T levels in KK and KK x Brangus bulls were 1.118±0.028 and 0.836±0.040 ng/ml, respectively, and differed significantly (p˂0.01). In addition, the average age at puberty was significantly (p˂0.01) earlier in KK bulls (18.0±0.37 months) than KK x Brangus bulls (23.5±0.33 months). In conclusion, the phenotypic and morphometric measurements in the current study showed that Malaysian KK cattle generally possess brown coat types with a smaller body size. The identification of an almost similar number of different genomic variants compared with the other Zebu cattle breeds clearly shows the Zebu origin of the Malaysian KK cattle. Secondly, the heterozygous ratio of SNPs and InDels obtained in the genome certainly indicates the presence of genetic variation in the KK cattle. The results of this study revealed that KK bulls were superior in terms of reproductive indices such as SC, testicular parameters, earlier age at puberty, conventional semen quality and SCC, and sperm DNA integrity as compared to KK × Brangus bulls. However, KK × Brangus bulls were better in terms of body weight and average daily weight gain than KK bulls. The phenotypic and genomic characterization are brand-new knowledge that will serve as the basis for future genetic research on the Malaysian KK breed. The knowledge generated from this study would serve as a tool for the genetic improvement of this potential breed to promote and expand the Malaysian beef industry in the future.